Statistical evaluation of CERCHAR Abrasivity Index (CAI) measurement methods and dependence on petrographic and mechanical properties of selected rocks of Pakistan - Majeed, Y.; Abu Bakar, M. Z. (Bulletin of engineering geology and the environment, 2016)
Forty-six rock units selected from various locations of Pakistan comprising of igneous, sedimentary and metamorphic rocks were subject to a comprehensive laboratory testing program consisting of two parts. The first part included CERCHAR abrasivity tests and measurement of physical rock properties including uniaxial compressive strength (UCS), Brazilian tensile strength (BTS), dry density, porosity, and P-wave velocity ( V p ). The second part involved petroghraphic thin section analyses of 40 selected abrasive and non-abrasive rock samples along with the determination of wear factors such as Schimazek’s F value and Rock Abrasivity Index (RAI). The CERCHAR abrasivity tests were conducted on sawn (CAI s ) and freshly broken (CAI fb ) rock surfaces employing top and side viewing methods for the measurement of wear flat of the stylus tip. This paper statistically confirms the previous work on the influence of wear flat measurement methods and rock surface conditions on the CERCHAR Abrasivity Index (CAI) values. It was found statistically that CAI s and CAI fb values measured from top view of the test stylus were 17 and 19 % higher, respectively, in comparison to CAI s and CAI fb values measured using side viewing stylus measurement technique. Further the correlations of CAI with RAI, Schimazek’s F value, petrographic, and physico-mechanical rock properties are also discussed.